The World is Beautiful: Conceptualizations of Aestheticization in Contemporary Thought - Staroselsky, Tatiana (2023)
Almost a century after Benjamin's famous diagnosis of a fascist aestheticization of politics, the concept of aestheticization has become central in many sociological, philosophical and artistic descriptions of the world in which we live. From the aestheticization of everyday life to the society of the spectacle, different authors have noted problematic forms of the presence of "the aesthetic" in areas that were in principle "non-aesthetic". In this work, I offer a cartography of some of these diagnoses as well as an interpretation of the senses that in each case acquires the very idea of aestheticization.